1999
DOI: 10.1111/1467-9817.00087
|View full text |Cite
|
Sign up to set email alerts
|

Causal connections in beginning reading: the importance of rhyme

Abstract: Profound misunderstandings of the implications of rhyme and analogy research (sometimes called`new phonics') for classroom teaching still appear regularly in the reading literature. It has been argued that`rhyme and analogy' researchers do not believe in teaching children grapheme-phoneme correspondences (Chew, 1997). Rhyme and analogy has also been branded as`analytic phonics', which is argued to be inferior to`synthetic' phonics (Watson and Johnston, 1999). Such misconceptions are confusing the debate over h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 60 publications
(132 reference statements)
3
137
1
6
Order By: Relevance
“…However, having identical rime phonology leaves the possibility open that stimulus groups differed in terms of phonotactic complexity or consistency of the word onset (initial phoneme or phoneme cluster). We therefore calculated initial phone frequency and transitional probabilities for the onset phonemes (see, e.g., Vitevitch & Luce, 1998, 1999. In addition, we verified whether the onsets of our items differed in terms of pronunciation and spelling consistency (type counts).…”
Section: Methodsmentioning
confidence: 93%
“…However, having identical rime phonology leaves the possibility open that stimulus groups differed in terms of phonotactic complexity or consistency of the word onset (initial phoneme or phoneme cluster). We therefore calculated initial phone frequency and transitional probabilities for the onset phonemes (see, e.g., Vitevitch & Luce, 1998, 1999. In addition, we verified whether the onsets of our items differed in terms of pronunciation and spelling consistency (type counts).…”
Section: Methodsmentioning
confidence: 93%
“…Other studies have confirmed the precedence of syllable awareness in French (Bruck, Genesee & Caravolas, 1997;Courcy, Béland & Pitchford, 2000;Ecalle & Magnan, 2002Lefebvre, Girard, Desrosiers, Trudeau, & Sutton, 2008). It would seem, in French, rhyme units are not as noticeable as in English for preschoolers (Goswami, 1999). This developmental difference has to be taken into account when planning phonological awareness activities for French kindergarteners.…”
Section: Phonological Processing Skillsmentioning
confidence: 93%
“…Clue word procedures examine the influence of phonological rime primes (e.g., pain-rain) compared to other types of primes that share beginning spelling sequences on children's decoding of upcoming words. In general, but not always (Bowey, Vaughan, & Hansen, 1998;Wood, 2002), children are better able to decode upcoming words that carry matching rimes than when they do not (Goswami, 1993(Goswami, , 1999. Training studies have been carried out that teach children to segment words explicitly into onsets and rimes and examining the ease with which these versus other combinations of words units are taught (Bruck & Treiman, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that most of the children in that study were past the phase of using word analogies in decoding. According to Goswami (1993Goswami ( , 1999, rime use represents an early phase of word decoding, and largely disappears by second grade. If this is correct, then studying individual differences in decoding in first grade may capture children for whom rimes are more available in word decoding.…”
Section: Methodsmentioning
confidence: 99%